2005
DOI: 10.1088/1464-4266/7/2/l01
|View full text |Cite
|
Sign up to set email alerts
|

Single-particle entanglement

Abstract: Using the approach to quantum entanglement based on the quantum fluctuations of observables, we show the existence of perfect entangled states of a single "spin-1" particle. We give physical examples related to the photons, condensed matter physics, and particle physics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
56
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 35 publications
(44 reference statements)
0
56
0
Order By: Relevance
“…The above discussion shows the utility of expectation values and statistical moments of observables in understanding quantum chaos. Uncertainty-based entanglement measures have been suggested outside the GE framework [34] providing links to important quantities such as the Wigner-Yanasi skew information [30,35] and a quantum analog of the Fisher information [36]. A dedicated study connectng GE to such measures will be presented elsewhere.…”
mentioning
confidence: 99%
“…The above discussion shows the utility of expectation values and statistical moments of observables in understanding quantum chaos. Uncertainty-based entanglement measures have been suggested outside the GE framework [34] providing links to important quantities such as the Wigner-Yanasi skew information [30,35] and a quantum analog of the Fisher information [36]. A dedicated study connectng GE to such measures will be presented elsewhere.…”
mentioning
confidence: 99%
“…As a matter of fact, violation of Bell-type conditions indicates the absence of hidden classical variables in quantum mechanics rather than entanglement. This allows us to conclude that nonlocality and violation of classical realism alone are not the essential sign of entanglement and that there is no physical prohibition for the existence of entanglement of local objects (particles) caused by quantum correlations of their intrinsic degrees of freedom [4], [5], [6], [7], [8].…”
Section: Introductionmentioning
confidence: 95%
“…This notion does not contain any quantification of distance between separated entangled parts of a quantum system. Thus, it seems to be natural to assume that quantum system with strongly correlated intrinsic parts may manifest entanglement independent of distance between the parts and hence even as a local object without spatial separation of parts [4], [5], [6], [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…Also, it was found that the spin squeezing is closely related to quantum entanglement [17][18][19][20][21][22], which plays an important role in quantum information and quantum computation. For an ensemble of two-level system, spin squeezing implies entanglement.…”
Section: Introductionmentioning
confidence: 99%
“…For an ensemble of two-level system, spin squeezing implies entanglement. At the same time, it was shown that a single spin-like system with S greater than 1/2 can also manifest entanglement [19][20][21], moreover, the single- * …”
mentioning
confidence: 99%